Hereditary hypotrichosis simplex of the scalp: A case report with 10 affected members in a family - Babu, Anuradha K.; Bai S, Jyoti (Indian Journal of Case Reports, 2018)
Hereditary hypotrichosis simplex of the scalp is an autosomal dominant disorder, characterized by sparse or absent scalp hairs without structural defects, in the absence of other ectodermal or systemic abnormalities. Hairs are usually normal at birth but thin progressively during childhood to become very sparse or may be absent by the third decade. Hair loss is confined only to the scalp with normal growth of facial and body hairs.